ARMED FORCES AND INTERVENTION IN TROPICAL AFRICA - Baynham, S.J.; Steyn, L. (Scientia Militaria - South African Journal of Military Studies, 2012)
"The Ghana Armed Forces, in co-operation with the police, have thought it necessary to take over the reins of power and to dismiss the former President, Kwame Nkrumah, the Presidential Commission and all Ministers, and to suspend the Constitution and to dissolve Parliament. This act has been necessitated by the political and economic situation in the country. The concentration of power in the hands of one man has led to the abuse of individual rights and liberty. Power has been exercised by the former President capriciously. The operation of the laws has been suspended to the advantage of his favourites and he has been running the country as his own personal property. "